(untitled) (Media Kesehatan Masyarakat Indonesia, 2019)
Exclusive breastfeeding is one of the foods that is very important for babies to support the optimal process of growth and development during the first 6 months.However, less than 70% of babies who get exclusive breastfeeding in Palembang. The study aimed to assess the pattern of infants weight gain among exclusive and nonexclusive breastfed babies. Cross sectional design was used in this study. Samples were mother’s who have babies aged 7-12 months in Seberang Ulu I Subdistrict, Palembang. Inclusion criteria were the last child/ first child, birth weight more than 2500 grams and mothers willing to be a respondent and babies with multiple births being exclusion criteria. The sampling technique used Proportionate Stratified Random Sampling. Independent T-Test showed that there was mean difference of weight gain in exclusively breastfed infants and non-exclusively breastfed infatns (Mean Difference: 433,63 gram; 95% CI: 27,8 to 839,4 grams). Conclusion was that exclusively breastfed infants had higher average weight gain than non-exclusively breastfed infants. Therefore, husband’s supportwas needed to providing motivation for mothers to exclusively breastfed until 6 months later.